Metabolic syndrome in patients with type 2 diabetes mellitus at Adama Hospital Medical College, Ethiopia: a hospital-based cross-sectional study - Charkos, Tesfaye Getachew; Getnet, Menberu (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Metabolic syndrome is one of the serious global public health problems. Its consequence was associated with a higher risk of heart attack and other cardiovascular diseases. However, the magnitude of metabolic syndrome among type two diabetes mellitus is not well understood, especially in developing countries like Ethiopia. Objective: To determine the magnitude of metabolic syndrome and associated factors among type two diabetes mellitus patients at Adama Hospital Medical College, Ethiopia, in 2022. Method: A facility-based cross-sectional study was conducted from September 1 to October 30, 2022. The data was collected through a self-administered questionnaire. A systematic random sampling method were used to select the participants. Data was entered using Epi Info version 7.2 and analyzed by SPSS version 23. Multivariable logistic regression was used to model this study. Statistical significance was set at P-values < 0.05. Result: A total of 237 participants were included in this study, with a response rate of 95.1%. Overall, the magnitude of metabolic syndrome was 53.2% (95% CI: 46.8 - 59.6), 41.3% (95% CI: 35.0 - 47.5), and 41.8% (95% CI: 35.5 – 48.1) based on 2009 harmonized, NCEP-ATP III and IDF criteria respectively. In multivariable logistic analysis, urban residence (AOR=3.07, 95% CI: 1.46-6.42), earning a high income (AOR=5.87 95% CI: 1.8-19.1), history of cardiac illness (AOR=3.33, 95% CI: 1.41-7.84), history of hypertension (AOR=2.65, 95% CI: 1.22-5.78), dyslipidemia (AOR=4.47, 95% CI: 1.96-10.19), current cigarette smoker (AOR=6.2, 95% CI: 1.7-22.93), sedentary activity (AOR=3.62, 95% CI: 1.68-7.82), use of palm oil (AOR=4.87, 95% CI: 2.06-11.51), and BMI ≥25 kg/m2 (AOR=3.36, 95% CI: 1.57-7.16) were significantly associated with metabolic syndrome. Conclusion: The findings of this study suggested that the magnitude of metabolic syndrome among T2DM patients was high. We found consistent results using the NCEP-ATP III and IDF criteria. Similarly, urban residence, high income, history of cardiac, history of hypertension, dyslipidemia, current cigarette smoker, sedentary activity, palm oil, and BMI ≥25 kg/m2 were significantly associated with metabolic syndrome.